Implementasi Kebijakan Perlindungan Anak Terhadap Kekerasan Anak di Kota Bandung Tahun 2023 - Indriani, Rhaisa; Nandang Alamsyah Delianoor; Novie Indrawati Sagita (Journal of Governance Innovation, 2024)
This research discusses the implementation of child protection policies against child abuse in Bandung City in 2023, focusing on the Office of Women's Empowerment and Child Protection (DP3A) and the Regional Technical Implementation Unit for Women and Children Protection (UPTD PPA). This research uses qualitative research with a narrative approach to describe the implementation of child protection policies.. The findings show that although the policy has been well implemented, there are barriers in human resources and costs. The limited number of employees and budget are challenges in achieving optimal child protection. However, community participation through the Community-Based Integrated Child Protection (PATBM) program and collaboration with various stakeholders have increased community awareness of child abuse issues. This research emphasizes the importance of continuous socialization and improved resources for the success of future child protection policies. Keywords: Child protection, child abuse, public policy, Bandung City, DP3A